IMPLEMENTATION OF SUSTAINED SILENT READING TO INCREASE FIFTH-GRADE STUDENTS’ READING INTEREST AT SDN 1 PEKANTINGAN - Rizka Amalia; Ani Nur Aeni; Cucun Sunaengsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The lack of students’ reading interest is indicated by many students who are more interested in playing with gadgets than reading a book. It is exacerbated by the condition of the library, which has been closed for approximately 5 years so it makes students less facilitated to read. The purpose of this paper is to find out how the implementation of Sustained Silent Reading increases fifth-grade students’ reading interest. The research was conducted at SDN Pekantingan 1 Cirebon. The method used was qualitative research method with study cases and data that are used and produced are descriptive data. Based on the AKM Kampus Mengajar’s pre-test dan posttest, the results indicate that there is a significant value. After implementing Sustained Silent Reading, the students dominantly achieve a significant value. Even though the posttest score did not reach 80, students still managed to obtain a significant score that was higher than the pretest. In conclusion, the implementation of Sustained Silent Reading is effective and can increase students' interest in reading.